2011
DOI: 10.1037/a0023770
|View full text |Cite
|
Sign up to set email alerts
|

One declarative memory system or two? The relationship between episodic and semantic memory in children with temporal lobe epilepsy.

Abstract: This double dissociation suggests that these 2 memory systems may develop independently in the context of temporal lobe pathology, perhaps related to differential effects of dysfunction in the lateral and mesial temporal lobe structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 99 publications
2
31
1
Order By: Relevance
“…In studies that grouped children with LTLE and children with RTLE together, children with epilepsy performed significantly lower than age-matched controls [99,102]. Studies that have compared pediatric patients with RLTE with those with LTLE on naming have had small sample sizes, with some studies showing significantly poorer naming in LTLE than in RTLE [102] with others showing similar patterns yet without statistically significant group differences [103,104], and with others showing no laterality effects at all [105].…”
Section: What Do We Know About Naming In Children With Epilepsy?mentioning
confidence: 99%
“…In studies that grouped children with LTLE and children with RTLE together, children with epilepsy performed significantly lower than age-matched controls [99,102]. Studies that have compared pediatric patients with RLTE with those with LTLE on naming have had small sample sizes, with some studies showing significantly poorer naming in LTLE than in RTLE [102] with others showing similar patterns yet without statistically significant group differences [103,104], and with others showing no laterality effects at all [105].…”
Section: What Do We Know About Naming In Children With Epilepsy?mentioning
confidence: 99%
“…One described a teenager with bilateral frontal foci who experienced a transitory "frontal lobe syndrome" during the [21] 21 n/r b n/a Cohen [23] n/a 24 11.21 6-16.3 Jambaque et al [24] n/a 28 n/r 7-14 Gonzalez et al [25] n/a 43 12.06 5-16 Nolan et al [26] 25 12.8 n/r 32 12.5 n/r Smith & Lah [27] n/a 66 13.55 5.17-18.17 Rzezak et al [28] n/a 19 14.46 8-16 Hershey et al [29] n/a 28 11.20 7-16 Gascoigne et al [30] n/a 23 12.5 n/r Oitment et al [31] n/a 41 n/r 6-18 Gonzalez et al [32] n/a 44 12.23 6-16 Gascoigne et al [33] n/a 21 12 [40] n/a 36 n/r 7-16 a n/a: no patients within this group included in study. b n/r: data not reported in paper.…”
Section: Executive Function In Children With Flementioning
confidence: 99%
“…These deficits are apparent on tasks of word learning and recall, memory for details of stories, recognition of faces, recognition and recall of abstract designs, and learning of and memory for spatial locations [23][24][25][26][27][28]. These children are adversely affected by interference over relatively short delay intervals [29].…”
Section: Memory In Children With Tlementioning
confidence: 99%
See 1 more Smart Citation
“…Our investigation is based on a large body of work that has indicated that the hippocampus contributes to and facilitates many forms of mental search (Addis & Schacter, 2011;Moscovitch, Cabeza, Winocur, & Nadel, 2016;Olsen, Moses, Riggs, & Ryan, 2012;Schiller, et al, 2015), including search through one's semantic knowledge base (Race, Keane, & Verfaellie, 2013;Ryan, Cox, Hayes, & Nadel, 2008;Sheldon & Moscovitch, 2012;Smith & Lah, 2011;Westmacott, Freedman, Black, Stokes, & Moscovitch, 2004;Westmacott & Moscovitch, 2003). A host of studies have found medial temporal lobe (MTL), and more specifically hippocampal, involvement during category fluency, a task that is often considered to be in the domain of semantic memory (e.g., Catheline, et al, 2015;Pihlajamaki, et al, 2000;Ryan, et al, 2008).…”
Section: Introductionmentioning
confidence: 99%